Wewenang Pemerintah Daerah Dalam Upaya Penanganan Konflik Sosial Antar Desa - Suneth, Safar; Pattinasarany, Yohanes; Picauly, Benjami Carel (PATTIMURA Law Study Review, 2025)
As a nation based on the rule of law, Indonesia places the supremacy of law as the primary foundation for the administration of national and state life. The implementation of regional and village autonomy, based on Law Number 23 of 2014 concerning Regional Government and Law Number 6 of 2014 concerning Villages, is a crucial instrument for strengthening local governance, including in the management of social conflict. Social conflicts, such as the case between Negeri Hitu and Negeri Wakal in Maluku, demonstrate that horizontal conflict between villages remains a recurring and complex issue. Regional governments have strategic authority in the prevention, management, and post-conflict recovery, as mandated by Law Number 7 of 2012 concerning Social Conflict Management. This study aims to examine the implementation of local government authority in handling inter-village social conflicts and analyze the legal consequences if local governments fail to exercise this authority. The method used is normative legal research with a statutory, conceptual, and case-based approach. The results indicate that the implementation of local government authority in handling social conflicts includes prevention, mediation, and recovery, while negligence can result in social disruption and legal consequences.